2018
DOI: 10.1007/s12039-018-1563-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical investigation of the nature of nucleobase-urea stacking interaction, a crucial driving force in RNA unfolding in aqueous urea

Abstract: Urea-assisted denaturation of protein and RNA has been shown to be a valuable tool to study their stabilities and folding phenomena. It has been shown that stacking interactions between nucleobases and urea are one of the driving forces of denaturation. In this study, the ability of urea to form unconventional stacking interactions with RNA bases is investigated by performing high-level quantum calculations (RI-MP2/aug-cc-pVDZ level) on a few thousands of model systems. Four systems were considered based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…As deciphered from spatial density maps analysis, along with conventional hydrogen bonding interactions, urea may be capable of forming NH-π and π-π interactions with nucleobases. Previous studies identified hydrogen bonding and stacking interactions as two main modes of interactions between urea and nucleobases 33,59 . We use certain geometric criteria to quantify these interactions and evaluate their respective probability distributions 37 .…”
Section: Resultsmentioning
confidence: 99%
“…As deciphered from spatial density maps analysis, along with conventional hydrogen bonding interactions, urea may be capable of forming NH-π and π-π interactions with nucleobases. Previous studies identified hydrogen bonding and stacking interactions as two main modes of interactions between urea and nucleobases 33,59 . We use certain geometric criteria to quantify these interactions and evaluate their respective probability distributions 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The quest to answer this challenging riddle has led to a number of experimental and theoretical studies to understand the unfolding mechanism. Earlier studies reported that urea induces changes in nucleic acid structures by forming favorable interactions with exposed surfaces of nucleobases compared with other regions, such as backbone, ribose, and phosphate groups (Hong et al 2004;Lambert and Draper 2012;Guinn et al 2013;Yoon et al 2013;Kasavajhala et al 2015;Miner and García 2017;Alodia et al 2018;Jaganade et al 2019).…”
Section: Experimental Evidence Of Urea-aromatic Stacking Interactionsmentioning
confidence: 99%
“…The ability of urea to form strong π −stacking interactions with nucleobases is intriguing. A recent extensive QM calculation investigated the importance of functional groups on nucleobases and studied the effect of urea orientations of the urea-nucleobase stacking interactions (Alodia et al 2018). Noncovalent stacking interactions were found to be the driving forces, and energetically, these interactions are dominated by dispersion effects.…”
Section: Experimental Evidence Of Urea-aromatic Stacking Interactionsmentioning
confidence: 99%
See 1 more Smart Citation